(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2023)
Infant mortality has been internationally defined as the number of deaths that occur in a pediatric population during the first year of life. In order to characterize infant mortality in the Hermanos Martínez Tamayo Polyclinic in the period from 2017 to 2021, a retrospective longitudinal study was conducted. The study universe was 12 deceased children under one year of age. Data collection was carried out through the registry and death records. The variables measured were maternal age and schooling, type of birth, birth weight and main causes of death. The year 2021 closed with an infant mortality rate of 15.2 per 1,000 live births. Early neonatal mortality was observed with 8.7 deaths per thousand live births, which was higher than the rest. Newborns with low birth weight and very low birth weight predominated, with 33.3%, respectively; deaths in infants under one year of age with low birth weight (41.7%) and prematurity (16.7%); the rate of early neonatal and late neonatal infant mortality, as well as low birth weight and cesarean deliveries. The ages of the mothers of the deceased ranged from 25 to 29 years old, mainly university graduates. The main causes of death were low birth weight and prematurity.